2010
DOI: 10.1124/dmd.110.032797
|View full text |Cite
|
Sign up to set email alerts
|

Formation Pathways of γ-Butyrolactone from the Furan Ring of Tegafur during Its Conversion to 5-Fluorouracil

Abstract: ABSTRACT:Tegafur (FT) is a 5-fluorouracil (5-FU) prodrug that has been clinically used for various cancer chemotherapies. The following metabolites of FT were identified in patients: 5-FU, fluoro-␤-alanine, and ␥-butyrolactone (GBL) and its acidic form, ␥-hydroxybutyrate (GHB). GBL/ GHB, which is probably generated from the furan ring of FT, inhibits tumor cell angiogenesis, contributing to the antitumor effect of FTbased therapies. In the present study, we identified the metabolites formed from the furan ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…; Yamamiya et al. ). Incubation mixture for hepatic microsomal metabolism contained FT, microsomes (1 mg protein/mL), 0.1 mmol/L CDHP, and an NADPH‐generating system consisting of 1.3 mmol/L β‐NADP + , 3.3 mmol/L glucose‐6‐phosphate, 3.3 mmol/L magnesium chloride, and 0.4 units glucose‐6‐phosphate dehydrogenase in 100 mmol/L Tris (pH 7.4).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Yamamiya et al. ). Incubation mixture for hepatic microsomal metabolism contained FT, microsomes (1 mg protein/mL), 0.1 mmol/L CDHP, and an NADPH‐generating system consisting of 1.3 mmol/L β‐NADP + , 3.3 mmol/L glucose‐6‐phosphate, 3.3 mmol/L magnesium chloride, and 0.4 units glucose‐6‐phosphate dehydrogenase in 100 mmol/L Tris (pH 7.4).…”
Section: Methodsmentioning
confidence: 97%
“…) (Yamamiya et al. ). FT is a chiral molecule and contains an asymmetric carbon at 2′‐position of its tetrahydrofuran moiety as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cytochrome P450 (CYP) and thymidine phosphorylase (TPase) in the liver are main contributors to the conversion of FT to 5‐FU [1–3]. As illustrated in Figure , our previous study clarified that CYP and TPase catalyze the 5′‐hydroxylation and 2′‐hydolysis of the tetrahydrofuran ring of FT, respectively, followed by sequential decomposition of the metabolites to 5‐FU [4]…”
Section: Introductionmentioning
confidence: 97%
“…As 5-FU formed from FT was subjected to extensive metabolism by dihydropyrimidine dehydrogenase contamination in enzyme preparations, a potent dihydropyrimidine dehydrogenase inhibitor, CDHP, was always added to prevent the unintended loss of 5-FU (Ikeda et al, 2000;Yamamiya et al, 2010Yamamiya et al, , 2013. The reaction mixture (0.1 ml) in the assay of insect microsomal metabolism contained FT, 50-100 pmol/ml CYP2A6, 0.1 mM CDHP, and an NADPH-generating system consisting of 1.3 mM b-NADP + , 3.3 mM glucose 6-phosphate, 3.3 mM magnesium chloride, and 0.4 units of glucose-6-phosphate dehydrogenase in 100 mM Tris-HCl (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…1, FT is a chiral molecule and contains an asymmetric carbon at the 29-position of its tetrahydrofuran ring. Our previous study clarified that cytochrome P450 (P450) and thymidine phosphorylase catalyze 59-hydroxylation and 29-hydrolysis, respectively, of the tetrahydrofuran ring of FT, followed by sequential decomposition of FT to 5-FU (Yamamiya et al, 2010). Recently we found that CYP2A6 was responsible for the enantioselective metabolism of FT. CYP2A6 catalyzed the conversion of both FT enantiomers to 5-FU most efficiently among P450 isoforms, and the intrinsic clearance of R-FT was significantly higher than that of S-FT in human liver microsomes (HLMs) (Damle et al, 2001;Yamamiya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%